Progress in the application of lecithins in water-in-oil emulsions. (December 2021) - Wang, Mengzhu; Yan, Weiqiang; Zhou, Yulin; Fan, Liuping; Liu, Yuanfa; Li, Jinwei
Abstract: Background: Long-term stability of water-in-oil (W/O) emulsions remains an urgent problem that limits their further application in the food industry. Moreover, the healthier products are increasingly required, which has inspired the entire or partial replacement of synthetic or semisynthetic emulsifiers in food products with natural amphiphilic lecithins. Therefore, it is essential to develop high-quality lecithins and better understand the factors that affect the emulsifying ability of lecithins in W/O emulsions. Scope and approach: This review presents the effects of the oil phase chain length, temperature and phospholipid composition on the spontaneous curvature of phospholipid monolayers, which determines the emulsifying ability of lecithins. The changes in phospholipid composition varied with different raw materials, and degumming methods and physical fractionation (deoiling methods and ethanol fractionation) were further described. Effects of proteins, polysaccharides, and inorganic salts in water as well as zein particles and polyglycerol polyricinoleate (PGPR) as coemulsifiers on the emulsifying ability of lecithins in W/O emulsions were analyzed and illustrated to provide new insights on the mechanism. Key findings and conclusions: Current studies have highlighted the entire or partial replacement of PGPR using lecithins or phosphatidylcholine-depleted lecithins in W/O emulsions and W/O/W double emulsions. Whey protein isolates or polysaccharides help to prevent coalescence for long-term stability. Furthermore, rapeseed and camelina seed using enzymatic and acid degumming respectively, were proposed to enrich phosphatidylethanolamine or phosphatidylinositol in lecithins for W/O emulsions. The present review may be helpful for selecting effective lecithins in W/O emulsions to promote practical application in food products. Highlights: W/O emulsion using lecithin/PGPR has similar stability to that only with PGPR. WPI is better than other proteins to cooperate with lecithins for W/O emulsion. PC-deleted lecithins have potential to be used alone in W/O emulsion. Lecithin based W/O emulsion is superior to prepare W/O/W emulsion.